Implementasi Coworking Space sebagai Pengembangan Fasilitas Perpustakaan Fakultas Kedokteran – Kesehatan Masyarakat dan Keperawatan Universitas Gadjah Mada - Sukirno Sukirno; Sri Junandi (Perpustakaan Nasional, 2021)
The Library of the Faculty of Medicine, Public Health and Nursing (FK-KMK) Gadjah Mada University is facing a changing user. Users are familiar with information technology with digital content, thus influencing their habits and behavior in using library facilities with laptops or smartphones. Users need adequate and comfortable facilities to work. Recognizing a shift in the habits and behavior of library users, FK-KMK seeks to develop library facilities with a Coworking Space approach. The formulation of the problem is how to implement Coworking Space in the development of FK-KMK UGM Library facilities. The purpose of the study was to determine the implementation of Coworking Space in the development of the FK-KMK UGM Library facilities. The methodology used in this research is descriptive qualitative approach, while the research variable is the implementation of Coworking Space for the development of FK-KMK Library facilities. The results showed that the implementation of Coworking Space for the development of library facilities is done by: changing the layout of the 1st floor, namely book collection shelves, tables, chairs and circulation services; painting the pillars on the 1st floor in bright colors; adding a reading space in the front porch of the FK-KMK Library; providing facilities for users in order to feel comfortable when learning or discussing in the library. The recommendation in this research is that Coworking Space encourage users to be comfortable when using the library facilities of FK-KMK UGM, so that maintenance and cleanliness are always carried out.